Strategi Penetapan Harga Jual Produk Melalui Perhitungan Cost of Goods Manufacture Menggunakan Process Costing Method - Adawia, Popon Rabia; Puspasari, Aprilia (E-Jurnal Akuntansi, 2021)
This study aims to help SMEs for shoe products in calculating the Cost of Goods Manufacture (COGM) appropriately using the process costing method as a strategy to determine the selling price of competitive shoes so that it is hoped that the business can continue. The research was conducted at one of the MSME Shoe Products, namely the Amira Collection, which is located in East Karawang. The comparative descriptive method is used to describe the production costs that occur in the production process including costs to buy raw materials, auxiliary materials, labor costs and factory overhead costs. The COGM calculation results show the variance (difference) between the company's COGM calculation system and the COGM calculation system using the process costing method where the company's COGM calculation results are lower. Keywords: Process Cost; Cost Of Goods Sold; Production Cost; Selling Price.